Technical Sheets of Regional Preparations as an instrument for the preservation of cultural identity - Jamille Góes da Conceição; Ana Gabriela de Freitas Barbosa; Isabella de Matos Mendes da Silva; Fernanda Freitas; Valéria Macedo Almeida Camilo (Universidade do Estado do Rio de Janeiro, 2021)
Introduction: The preservation of traditional foods makes available, to the market, foods with a symbolic character, representatives of the food heritage, and with specific qualities. Thus, the standardization of the production process through the Technical Data Sheet for Preparation represents a viable alternative to preserve the regional characteristics of the products. Objective: This study aimed to prepare Technical Data Sheets for the Preparation of regional products as an instrument to promote quality and preserve local practices and knowledge of preparations made by a cooperative in the Baixo Sul region, Bahia. Method: Initially, an on-site visit was carried out to characterize the food production sites and the groups of farmers participating in the cooperative; later, a form was applied to establish the selection criteria for the preparations. Then, five products were chosen to be standardized; soon after, the production was monitored, followed by the preparation of Technical Data Sheets. Results: Technical Sheets for the Preparation of genipap candy, peanut beiju, sugar-free banana biscuit, gum biscuit, and cocoa jelly were prepared. The production is 100% artisanal and has significant cultural value, as they are made from raw materials present in the territory, following tradition, whose culinary practices have been shared among family members for generations. Conclusion: The preparation of Technical Data Sheets made it possible to standardize regional preparations, contributing to quality, as well as the reduction of wasting of raw materials, using available resources in the region, reducing costs, local development, and preservation of cultural identity preparations made by the cooperative.